Estados estacionários múltiplos de fluorescência e fosforescência em pequenos domínios de moléculas orgânicas derivados de fenazina - Gustavo Henrique Rocha Soares (2019)
In this M.Sc. in Physics is presented the experimental results of our study of the optical properties of dropcast films containing a set of few domains of organic interacting derivative molecules of Phenazine, which were distributed randomly in an optically inert matrix of Zeonex. Low concentration of organic molecules in a host matrix involves steric interactions of them with the Zeonex molecules. Small domains of these few organic molecules at different molecular conformations would be created and would be randomly distribute in the matrix, originating a heterogeneous system. Spectroscopic measurements in this type of system allow the acquisition of new information about the molecular conformations of few interacting molecules and no more an average contribution of the sum of emissions from many molecular conformations. It is well known that phenazine compounds, in particular the phenazine (9,10-diazaanthracene), present very weak fluorescence and relatively strong phosphorescence. This fact shows that singlet states Sn excited in phenazines relax to some other electronic state at shorter times than those related to natural radiative decays (Sn → S0). The main path of such conversion is the intersystem crossing to triplet states. In addition, non-radiative decays, involving energy loss through excitation of vibrational modes, occur between triplet states which harm the intensity of phosphorescent emission in these compounds, especially at high temperatures. This work will discern about optical steady-state emission properties at room and at low temperatures of dropcast films of phenazine derivative blends in a Zeonex matrix at relatively low concentrations. Zeonex, a cycloolefin polymer (ZEON Corporation), is an optically inert material and it has been used as a host to induce a dispersion of derivative phenazine organic molecules, limiting their intermolecular interactions, and, at the same time, imposing greater molecular stiffness to them. The absorption and emission properties of the derivative phenazine molecules will not be modified by the presence of the Zeonex matrix. The higher matrix rigidity will prevent non-radiative decays, avoiding the lost of energy by excitation of vibrational modes even at room temperature, which will favor the phosphorescent emissions. fluorescent and phosphorescent emissions from different molecular conformations will be discussed in this work.